Radiocarbon chronology and settlement patterns in the Bronze Age of the Qaidam Basin, Northwestern China - Ben Li; Jian Ma; Honghai Chen; Meng Guo; Jiyuan Li; Meng Ren; Hongxian Yan; Yongming Xiao; Marcella Festa (Scientific Reports)
Abstract Prehistoric settlement patterns on the Tibetan Plateau, particularly in the Qaidam Basin, have drawn significant scholarly interest. Yet, limited data have hindered a comprehensive understanding the Bronze Age chronology and landscape exploitation in this region. This paper presents 24 newly obtained radiocarbon dates from eight archaeological sites within the Qaidam Basin on the Tibetan Plateau. Integrated with existing 14 C data and spatial analysis, these findings reveal an overall continuous occupation of the basin from ca. 3600–2500 calBP, with a gradual shift from expansive lowland settlements to smaller, ephemeral high-altitude structures, identified around 3350 calBP. This change is consistent with demonstrated periods of climate degradation which likely drove strategic adaptations in landscape management and subsistence methods. Overall, this research not only establishes a more robust chronology for the Qaidam Basin’s Bronze Age, but also advances the discussion on human-environment interactions in high-altitude areas during late prehistory.